2021
DOI: 10.3390/ijerph18052762
|View full text |Cite
|
Sign up to set email alerts
|

Does Lung Ultrasound Have a Role in the Clinical Management of Pregnant Women with SARS COV2 Infection?

Abstract: Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) infection is a major health threat. Pregnancy can lead to an increased susceptibility to viral infections. Although chest computed tomography (CT) represents the gold standard for the diagnosis of SARS-CoV-2 pneumonia, lung ultrasound (LUS) could be a valid alternative in pregnancy. The objectives of this prospective study were to assess the role of LUS in the diagnosis of lung involvement and in helping the physicians in the management of affected p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 88 publications
1
7
0
Order By: Relevance
“…Our data agree with those presented in the study of Moro et al, which first noted that the greater was the parenchymal involvement, the greater was the severity of COVID-19 pneumonia (16). Porpora et al also found a positive correlation between LUS score and CT scan score (17). They proposed to manage patients with COVID-19 based on the clinical status and the pulmonary involvement with LUS.…”
Section: Discussionsupporting
confidence: 92%
“…Our data agree with those presented in the study of Moro et al, which first noted that the greater was the parenchymal involvement, the greater was the severity of COVID-19 pneumonia (16). Porpora et al also found a positive correlation between LUS score and CT scan score (17). They proposed to manage patients with COVID-19 based on the clinical status and the pulmonary involvement with LUS.…”
Section: Discussionsupporting
confidence: 92%
“…Last year, M.G. Porpora et al evaluated the role of LUS in the decision-making process, studying the correlation between LUS score and CT score carried out after delivery, which strengthens the reliability of LUS as an alternative diagnostic method to CT in pregnant women [20]. Chest CT was performed after delivery in patients with high LUS score or persistent respiratory symptoms and showed a score up to 4 with an involvement <10% in five cases, a score between 5 and 8 with involvement of 10-25% in three women, while in the patients with a LUS score of 23, CT showed 60-70% lung involvement with a score of 16.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Chest CT was performed after delivery in patients with high LUS score or persistent respiratory symptoms and showed a score up to 4 with an involvement <10% in five cases, a score between 5 and 8 with involvement of 10-25% in three women, while in the patients with a LUS score of 23, CT showed 60-70% lung involvement with a score of 16. Even if the CT findings were more precise than LUS in defining pulmonary impairment, these results suggest a positive correlation between LUS and CT [20]. CT and LUS images of 39 pregnant patients were retrospectively collected and compared by Q. Deng et al [21].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…In conclusion, lung US could serve as a valuable tool for the detection and follow-up of lung lesions in COVID-19 pneumonia and also provide supplemental imaging information for currently recommended radiological examinations, with the advantages of being radiation-free, flexibility, and cost effective [ 30 ], as an alternative to chest CT. Although lung US cannot replace CT, which is the gold standard for lung evaluation, lung US may be considered a reliable tool in pregnancy [ 41 ].…”
Section: The Role Of Lung Ultrasound In Covid-19 Diseasementioning
confidence: 99%